5(x+3)+2=-8(x+7)

Simple and best practice solution for 5(x+3)+2=-8(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+2=-8(x+7) equation:



5(x+3)+2=-8(x+7)
We move all terms to the left:
5(x+3)+2-(-8(x+7))=0
We multiply parentheses
5x-(-8(x+7))+15+2=0
We calculate terms in parentheses: -(-8(x+7)), so:
-8(x+7)
We multiply parentheses
-8x-56
Back to the equation:
-(-8x-56)
We add all the numbers together, and all the variables
5x-(-8x-56)+17=0
We get rid of parentheses
5x+8x+56+17=0
We add all the numbers together, and all the variables
13x+73=0
We move all terms containing x to the left, all other terms to the right
13x=-73
x=-73/13
x=-5+8/13

See similar equations:

| 42=2(12+a) | | 62=-3a+2 | | 6x+7=4x-6 | | 2(x+3)-3x=5-2x+1 | | -3-14x=319 | | 12x-12-11x=2 | | −4=z+3 | | 4.4x=-30.8 | | k=−4 | | x+1/2-x/4=5/2 | | m/14-9=-10 | | 10p^2-3=-12p | | x−2.8=1.6 | | 4x+5=23-3x+3 | | 42(4/7x=1/6) | | 33x=94x | | 2=9+n/3 | | 36-18n=50n+70 | | -5=-10x+25 | | 8x+4=−4+6x+18 | | -25+4(2x+5)=-51 | | -0.16x+0.02x=0.1x+0.4 | | 3x+6=-2x-6 | | 9x-x+3=19 | | 45y=450 | | 12m+12=32 | | 7x(7x-12=-72 | | 3w=68 | | (6x+5)4x=(4x×45)4x | | Y-10=4o | | 2(x+2)^2=2x(x+2) | | 2(x+2)^2=0 |

Equations solver categories